A chest wall mass after breast carcinoma surgery: a simple diagnosis?. Issue 4 (2nd May 2017) - Minervini, Fabrizio; Greuter, Ladina; Kestenholz, Peter; Schneider, Tino; Gutmann, Christine; Dutly, André Emanuel
Abstract : Tuberculosis affects pulmonary and extra‐pulmonary sites with a multitude of differing presentations. The involvement of thoracic wall is a rare entity. We report the case of a patient who had a tumefaction on the right chest wall 6 months after a right breast mastectomy. After an initial radiological suspicion of malignancy, we detected intraoperatively an abscess in which histologic examination revealed granulomas with multinucleated giant cells. Abstract : Chest wall tuberculosis is a very rare condition with few cases reported in the literature. The aim of this article is to report a patient operated for chest wall tumefaction and to review the literature.